Bone marrow image segmentation based on multilevel thresholding - Robiyanti, Adollah; Elsie Usun, Francis; Mohd Yusoff, Mashor, Prof. Dr.; Nor Hazlyna, Harun (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/